1991
DOI: 10.1007/bf02633532
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in English and Japanese women: Prognostic significance of sinus histiocytosis and germinal center hyperplasia in axillary lymph nodes

Abstract: A prospective study of comparable Japanese and British breast cancer patients treated by radical mastectomy confirmed previously reported findings that sinus histiocytosis and germinal center hyperplasia are more frequently seen in axillary lymph nodes from Japanese than in those from British patients. In Japanese, but not British, cases of either of these two morphologic findings had favorable prognostic significance for recurrence. Sinus histiocytosis also had favorable prognostic significance in Japanese ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Indeed, the only pathological difference that has been previously noted in these 2 groups of patients is in histological features of the axillary lymph nodes. The incidences of both sinus histiocytosis and germinal center activity were found to be significantly higher in Japanese than in British women (Friedell et al, 1991).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, the only pathological difference that has been previously noted in these 2 groups of patients is in histological features of the axillary lymph nodes. The incidences of both sinus histiocytosis and germinal center activity were found to be significantly higher in Japanese than in British women (Friedell et al, 1991).…”
Section: Discussionmentioning
confidence: 79%
“…Recent follow-up data were only available for the Anglo patients. The results of other comparative studies of clinical, biochemical, histopathological features and prognosis carried out on these patients have been reported previously Friedell et al, 1991;Allen et al, 1991;Miura et al, 1991;Sato and Suchi, 1991;Moore et al, 1991). For the present study, patients with pure in situ carcinoma and minimally invasive carcinoma were excluded, as were cases where insufficient material remained in the tissue blocks for immunohistochemical evaluation of c-erbB2 and p53 proteins.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigators have found that Japanese patients with breast cancer have a better survival than American or British patients (Wynder et al, 1963;Morrison et al, 1976;Friedel et al, 1991). There are several limitations to these hospital-based studies.…”
Section: Discussionmentioning
confidence: 98%
“…Improved survival from this cancer in the UK may be due to increased social interest, advances in diagnosis according to the NHS Breast Screening Programme, and development of adjuvant endocrine therapy and chemotherapy (Beral et al, 1995;Kobayashi, 2004). There is also strong evidence to suggest a population-dependent variation in the biology of breast cancer, such as ER status, p53 gene mutation, HER-2/neu, S-phase fraction, lymphatic infiltration, sinus histiocytosis, and certain histological patterns (Sakamoto et al, 1981;Friedel et al, 1991;Elledge et al, 1994;Merchant et al, 1999). Differences in these biologic characteristics do not explain the relatively high survival rate of Japanese breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%